Efektifitas Penggunaan Media Pembelajaran Crossword Puzzle Terhadap Kemampuan Numerasi Siswa Sekolah Dasar - Wijayanti, Vita; Sari, Intan Putri Permata; Nuzula, Firdausi; Fuadi, Yasfian Alfi; Rozak, Abd. (Supermat : Jurnal Pendidikan Matematika, 2024)
This research was carried out as part of a campus teaching program aimed at improving students' literacy and numeracy skills. The main focus of the research is to eval____uate the effectiveness of using Crossword puzzle learning media in improving students' numeracy skills. The method used was One-Group Pre-test Post-test Design involving 23 class V students from SDN Sukodadi 1. Data was collected through pre-test and post-test to assess students' understanding of numeracy before and after using the Crossword puzzle . Data analysis was carried out by comparing the average pre-test and post-test scores using the paired t test. The results of the analysis show a significant increase with a significance value of 0.000 (Sig < 0.05), indicating that the use of Crossword puzzle s is effective in improving students' numeracy skills.